Youth education investment and labor market outcomes in the Philippines survey report. (Southeast Asia working papers., 2019)
The survey focused on students choice of track in senior high school academic, technical vocational and livelihood, sports, or arts and design their choice of college course, and their occupational preferences and expectations. It was conducted by the Asian Development Bank in collaboration with the Philippine Department of Education. Its results highlight the most influential considerations and information sources for students and households. This report aims to help enhance career guidance programs and long term labor market outcomes.